The pyrin inflammasome: from sensing RhoA GTPases-inhibiting toxins to triggering autoinflammatory syndromes. Issue 3 (28th March 2018) - Jamilloux, Yvan; Magnotti, Flora; Belot, Alexandre; Henry, Thomas
Abstract: Numerous pathogens including Clostridium difficile and Yersinia pestis have evolved toxins or effectors targeting GTPases from the RhoA subfamily (RhoA/B/C) to inhibit or hijack the host cytoskeleton dynamics. The resulting impairment of RhoA GTPases activity is sensed by the host via an innate immune complex termed the pyrin inflammasome in which caspase-1 is activated. The cascade leading to activation of the pyrin inflammasome has been recently uncovered. In this review, following a brief presentation of RhoA GTPases-modulating toxins, we present the pyrin inflammasome and its regulatory mechanisms. Furthermore, we discuss how some pathogens have developed strategies to escape detection by the pyrin inflammasome. Finally, we present five monogenic autoinflammatory diseases associated with pyrin inflammasome deregulation. The molecular insights provided by the study of these diseases and the corresponding mutations on pyrin inflammasome regulation and activation are presented. Abstract : The pyrin inflammasome: when an innate immune complex detecting bacterial toxins causes autoinflammatory syndromes.